1999
DOI: 10.1152/ajpregu.1999.276.6.r1653
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to febrile temperature upregulates expression of pyrogenic cytokines in endotoxin-challenged mice

Abstract: Fever is a phylogenetically ancient response that is associated with improved survival in acute infections. In endothermic animals, fever is induced by a set of pyrogenic cytokines [tumor necrosis factor-α (TNF-α), interleukin (IL)-1, and IL-6] that are also essential for survival in acute infections. We studied the influence of core temperature on cytokine expression using an anesthetized mouse model in which core temperature was adjusted by immersion in water baths. We showed that raising core temperature fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 29 publications
6
56
0
3
Order By: Relevance
“…It has been demonstrated that fever, one brain-mediated sickness response, is beneficial to the health/survival of an infected organism (Blatteis, 1986;Kluger et al, 1975), most likely because elevated core body temperature increases antimicrobial responses of immune cells (Jiang et al, 1999;Roberts, 1991;Sebag et al, 1977). Due to the enormous metabolic demands of elevating body temperature, it has been suggested that other brain-mediated sickness responses function to minimize other energy usages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that fever, one brain-mediated sickness response, is beneficial to the health/survival of an infected organism (Blatteis, 1986;Kluger et al, 1975), most likely because elevated core body temperature increases antimicrobial responses of immune cells (Jiang et al, 1999;Roberts, 1991;Sebag et al, 1977). Due to the enormous metabolic demands of elevating body temperature, it has been suggested that other brain-mediated sickness responses function to minimize other energy usages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic nature of TNF␣ has lead to the evolution of stringent and redundant regulatory mechanisms imposed at transcriptional, translational, and posttranslational levels (6 -11). We reported that exposure to febrile range hyperthermia suppresses TNF␣ expression in murine peritoneal macrophages, Kupffer cells, precision-cut liver slices, the murine Raw 264.7 macrophage cell line, human monocyte-derived macrophages, and the THP1 monocyte cell line (10,(12)(13)(14)(15)(16). We showed that the predominant mechanism of suppression of TNF␣ expression is by an abrupt and early cessation of TNF␣ transcription, and that the TNF␣ gene sequence between Ϫ85 and ϩ138 is sufficient to confer temperature responsiveness in murine macrophages (15).…”
Section: Tumor Necrosis Factor-␣ (Tnf␣)mentioning
confidence: 99%
“…Solid organs harvested for transplantation may be stored at more extreme hypothermia for prolonged periods prior to transplant. Work from our group and others has shown that modest changes in temperature within the physiological range alters expression level of certain genes with important physiologic and clinical consequences (Cahill et al 1996;Chen et al 1997Chen et al , 2006Chen et al , 2009Wang et al 1998;Jiang et al 1999aJiang et al ,b, 2000Fairchild et al 2000;Singh et al 2000Singh et al , 2002Singh et al , 2008Hasday et al 2003;Ellis et al 2005;Appenheimer et al 2007;Vardam et al 2007;McClung et al 2008;Nagarsekar et al 2008Nagarsekar et al , 2012Cooper et al 2010a,b;Lipke et al 2010Lipke et al , 2011Fisher et al 2011;Maity et al 2011;Tulapurkar et al 2011Tulapurkar et al , 2012Zhang et al 2012;Gupta et al 2013). Most of the studies of temperature-dependent gene expression have focused on transcriptional regulation (Cahill et al 1996(Cahill et al , 1997Chen et al 1997;Singh et al 2008;Cooper et al 2010a,b;Maity et al 2011;Zhang et al 2012), but post-transcriptional regulation by small noncoding RNAs like microRNA (miRNA) may be as important as transcriptional regulation for ∼30% of all genes (Lewis et al 2005).…”
Section: Introductionmentioning
confidence: 99%